A Comparative Analysis of Software Quality and Development Cost for a Community Elderly Database System A Case Study Comparing Four Development Approaches Using the Personal Software Process (PSP) - Nachiangmai, Wacharapong; Wunchaisatira, Danuphon; Yodnin, Satianpong; Somboon, Irin (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
As Thailand fully transitions into an aging society, the development of information technology to support elderly care has become essential, particularly for safety-critical functions such as location tracking and emergency alerts. This research aims to analyze and compare software quality and development costs using the Personal Software Process (PSP) framework. The study compares four development approaches: (G1) Solo Waterfall, (G2) Pair Programming, (G3) Code Review, and (G4) Test-Driven Development (TDD). The experiment involved third-year software engineering students developing three core functions: health record management, Google Map location tracking, and emergency help requests, utilizing tools such as Express JS, MySQL, Mocha, and Chai. Empirical results indicate that G4 (TDD) achieved the highest software quality, with a Defect Removal Efficiency (DRE) of 100% in critical functions and the lowest Defect Density (12.93-22.73 per KLOC), despite higher initial time costs due to test case development. Conversely, G1 (Waterfall) exhibited the lowest initial labor cost (1,585 THB) but recorded the highest post-run defects, leading to significant long-term hidden costs. G2 recorded the highest human resource costs as it required two developers for a single task. The suitability analysis concludes that TDD and Code Review are the most appropriate approaches for safety-critical systems to ensure data integrity and the life safety of the elderly.